Religion among we the people : conversations on democracy and the divine good - Gamwell, Franklin I. (State University of New York Press, 2015)
Franklin I. Gamwell holds that democracy with religious freedom is dependent on metaphysical theism. Democratic politics can be neutral to all religious convictions only if its constitution establishes a full and free discourse about the ultimate terms of justice and their application to decisions of the state, and the divine good is the true ground of justice. Notabley, Gamwell's view challenges virtually all current accounts of democracy with religious freedom.